The Quasi-Resonant Structure and Control Strategy of a Photovoltaic Flyback Grid-Connected Microinverter - Zipei, Cao; Annisa, Jamali; Abdullah, Yassin; Ya, Huang (MDPI, 2024)
This study proposes a topology structure for a flyback grid-connected inverter with a compensation capacitor. The addition of the compensation capacitor structure increases the harmonic oscillation period and reduces the switching frequency. Additionally, a control strategy for the microinverter is proposed. By using an accurate peak current reference curve, the system ensures precise turn-off signals, thus reducing the harmonic content of the grid-connected current. Simultaneously, the multi-valley turn-on strategy is employed to address the issue of high switching frequency, minimising the impact of energy. The proposed topology structure and control methods are modelled, simulated, and tested to validate the feasibility of the microinverter topology structure and the effectiveness of the control strategy, achieving a maximum efficiency of 95.2% and controlling the total harmonic distortion (THD) below 2.39%. Compared to other microinverter products, it is more efficient and stable.